PENGEMBANGAN MUTU KINERJA GURU MELALUI KEPEMIMPINAN TRANFORMASIONAL KEPALA SEKOLAH DI ERA DIGITALISASI - Syarifudin Zaidan, Akmal; Minarti, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of transformational leadership of school principals in improving teacher performance quality in the digital era. The research method employed is library research by reviewing various scientific journals, books, research reports, and relevant educational policies. The findings indicate that transformational leadership plays a crucial role in creating a conducive school climate, motivating teachers to innovate, and utilizing digital technology in the learning process. Three key aspects identified as essential for strengthening teacher performance are adaptation to rapid changes, improvement of data literacy, and teacher well-being and work-life balance. The effective application of transformational leadership encourages the enhancement of teachers’ pedagogical and professional competencies, strengthens collaboration, and ensures that learning remains relevant to students’ needs in the digital age. This study contributes to a deeper understanding of how school principals can act as change agents by integrating vision, motivation, and digital innovation to empower teachers. Therefore, transformational leadership serves as a strategic approach to improving education quality and addressing the complex challenges of 21st-century education in a sustainable manner.